Assessing Color-Neutral Racial Attitudes of Faculty at Hispanic-Serving Institutions. (July 2020) - Garcia, Gina A.; Koren, Emily R.; Cuellar, Marcela G.
The purpose of this exploratory quantitative study was to assess the color-neutral racial attitudes of faculty at Hispanic-Serving Institutions (HSIs) and to investigate the connection to knowledge and skills for teaching minoritized students. HSIs enroll a large percentage of racially minoritized students, and faculty must be able to assess their attitudes about institutional discrimination and blatant racial issues, which may affect how they teach students of color. We used The Color-Blind Racial Attitudes Scale and Multicultural Teaching Competency Scale to collect data from faculty at 10 HSIs across the United States. Results show that faculty in our sample have low levels of color-neutral racial attitudes, meaning they are aware of racial issues facing students, with slight differences by race, gender, and academic discipline. Moreover, higher color-neutral racial attitudes are associated with lower knowledge and skills for teaching minoritized students. Implications for enhancing "servingness" at HSIs are offered.